(untitled) (Medico Legal Update, 2021)
Adulteration in pharmaceutical products is common all over the world particularly in pharmaceutical oral dosage forms like tablets, gelatin capsules. According to previous studies there were many techniques are available to recognize counterfeit medicines. Near Infrared Spectroscopic techniques is widely used in this area due to its numerous advantages. In this work, we used ASD Field Spec4 Spectroradiometer having broad spectral range (350-2500 nanometer) and its supporting software’s to create Spectral library of pharmaceutical common drug Paracetamol and some basic excipients used in pharmaceutical industry as formulation process of tablets and capsules and finally also showed the absorption bands of Paracetamol API and Excipients.